Pengembangan SDM dan Pemasaran Produk Usaha Candi Silver Di Desa Nagasepaha Dalam Meningkatkan Keunggulan Bersaing - Seri Naraswari, Dewa Ayu; Agung Maesa Ardanari, I Gusti Ayu; Dewi, Mertyani Sari; Pasek, Gede Widiadnyana (Jurnal Pengabdian Masyarakat (ABDIRA), 2023)
This service aims to improve the ability to use digital marketing through the application of a training model. This service was carried out on one of the MSME actors in Nagasepaha Village, Buleleng Regency, Buleleng District, Bali. This type of service is community education and training service with a three-stage procedure, namely: (1) Preparation stage, (2) Implementation stage and, (3) Evaluation and monitoring stage. The data collection method used in this service is through observation. The data collection process through this observation uses direct interview techniques. The results of the service show that MSME actors produce a change by being able to use digital marketing from the training that has been provided which aims to promote the products of their skills, so it can be concluded that the application of the training model can increase self-confidence and compete with the same type of MSMEs.